Об изометрических представлениях полугруппы Z₊\{1} - В. А. Тепоян (Հայաստանի ԳԱԱ)
В работе исследуются изометрические представления полугруппы Z+\{1}. Вводится понятие инверсного представления и дается полное описание (с точностью до унитарной эквивалентности) таких представлений этой полугруппы. Исследуется некоторый класс неприводимых не инверсных представлений (β-представления полугруппы Z+\{1}. In this paper we study isometric representations of the semigroup Z+\{1}. The notion of inverse representation is introduced and a complete (to within unitary equivalence) description of such representations of that semigroup is provided. A class of irreducible non-inverse representations (β-representations of the semigroup Z+\{1}) is described.
Keywords: General Works; Science; Mathematics